2011
DOI: 10.1002/syn.20990
|View full text |Cite
|
Sign up to set email alerts
|

Slow phasic and tonic activity of ventral pallidal neurons during cocaine self‐administration

Abstract: Ventral pallidal (VP) neurons exhibit rapid phasic firing patterns within seconds of cocaine-reinforced responses. The present investigation examined whether VP neurons exhibited firing rate changes: 1) over minutes during the inter-infusion interval (slow phasic patterns) and/or 2) over the course of the several-hour self-administration session (tonic firing patterns) relative to pre-session firing. Approximately two-thirds (43/54) of VP neurons exhibited slow phasic firing patterns. The most common pattern w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 63 publications
0
36
1
Order By: Relevance
“…Analysis of neural data was conducted using SciWorks software (Datawave Technologies) as described in detail elsewhere (Root et al, 2012). Briefly, the software was used to isolate neural waveforms from ambient noise and to discriminate different neurons recorded by the same microelectrode.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of neural data was conducted using SciWorks software (Datawave Technologies) as described in detail elsewhere (Root et al, 2012). Briefly, the software was used to isolate neural waveforms from ambient noise and to discriminate different neurons recorded by the same microelectrode.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…Ventral striatopallidal neurons exhibit fluctuations in firing rate during the minutes between self-infusions of cocaine (termed “slow-phasic firing patterns”; Peoples and West 1996; Nicola and Deadwyler, 2000; Root et al 2012). Over a longer timescale, across the entire session (termed “tonic firing patterns”), both accumbal and VP neuron firing rates correlate with self-administered cocaine levels.…”
Section: 0 Introductionmentioning
confidence: 99%
“…The nAcc neurons also exhibit slow-phasic and tonic changes in firing rate that correlate with the pharmacological effects of cocaine, and do not correlate with the rapid phasic firing patterns (Fabbricatore et al, 2010). Furthermore, slow phasic pharmacologic and rapid phasic behavioral firing patterns are similarly processed in downstream accumbal targets (ventral pallidum and lateral preoptic area; Root et al, 2012, 2013; Barker et al, 2014). These dissociable fast and slow signaling patterns in the accumbens are consistent with findings suggesting that glutamate and dopamine each have specific roles in addiction-associated behaviors (Birgner et al, 2010; Alsiö et al, 2011).…”
Section: Functional Diversity By Vta Neuronsmentioning
confidence: 99%
“…Heterogeneous VP responses were also observed during operant responding for cocaine. Interestingly, most phasically active VP neurons were found to reduce firing rate during approach behavior (Root et al, 2012). This response is similar to the predominant response of NAc neurons during appetitive responding (Taha & Fields, 2006), and is not the predicted result of VP disinhibition resulting from reduced GABA input by the NAc.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, several studies have demonstrated that the VP not only plays a critical role in the normal expression of hedonic responses, but also in ingestive behavior (Gong, Neill, & Justice, 1997; Stratford & Wirtshafter, 2013), and drug seeking (Kemppainen, Raivio, & Kiianmaa, 2012; Mahler et al, 2014; Stefanik, Kupchik, Brown, & Kalivas, 2013). Furthermore, in vivo electrophysiological experiments have aligned specific patterns of VP neuronal activity with hedonic processing and drug-seeking behavior (Root, Fabbricatore, Ma, Barker, & West, 2010; Root et al, 2012; Root et al, 2013; Smith, Berridge, & Aldridge, 2011). Based on this intimate relationship, and coincident function, we hypothesized that VP neurons encode hedonic information and are sensitive to changes of hedonic values as a result of cocaine-induced conditioned taste aversion.…”
Section: Introductionmentioning
confidence: 99%